2013
DOI: 10.1007/s00394-013-0633-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies and demographic determinants of breastfeeding and DHA supplementation in a nationwide sample of mothers in Germany

Abstract: Breastfeeding initiation and duration of exclusive breastfeeding in Germany need to be improved. Professional counselling and support, with a focus on mothers from lower social classes, appears necessary to increase current rates of breastfeeding initiation, duration, and exclusiveness, but also to ensure a sufficient supply with DHA in pregnant and lactating women, particularly in women with low fish consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“…Previous studies in developed countries have consistently found that key social determinants of health, particularly lower maternal education and socioeconomic status are associated with lower rates of breastfeeding initiation and increased rates of in-hospital formula supplementation. 14,16,17,28,31 Notably in our study, the estimated effect of exclusive breastfeeding in hospital was twice as great for women with lower education, compared with women with higher educational attainment. While highly educated women experienced a 16% reduced risk of breastfeeding cessation if they exclusively breastfed in hospital, women with lower education experienced a 35% reduced risk.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies in developed countries have consistently found that key social determinants of health, particularly lower maternal education and socioeconomic status are associated with lower rates of breastfeeding initiation and increased rates of in-hospital formula supplementation. 14,16,17,28,31 Notably in our study, the estimated effect of exclusive breastfeeding in hospital was twice as great for women with lower education, compared with women with higher educational attainment. While highly educated women experienced a 16% reduced risk of breastfeeding cessation if they exclusively breastfed in hospital, women with lower education experienced a 35% reduced risk.…”
Section: Discussionmentioning
confidence: 57%
“…We found that full breastfeeding prevalence ranged from 2 to 11 percent at 6 months in the ethnic groups. Our rates of full breastfeeding are lower than the rates of exclusive breastfeeding observed in most countries in Europe . The reasons behind these low full breastfeeding rates are likely to be complex but reflect practices in the two study hospitals before the implementation of Baby Friendly Hospital Initiative (BFHI) guidelines in 2012.…”
Section: Discussionmentioning
confidence: 70%
“…Risk factors for early weaning have been widely studied in the West, with few studies from Asia. Some of the reported risk factors include smoking, low maternal education, use of pacifier, and return to work . As more mothers return to the work force after delivery, the mode of feeding breast milk (direct breastfeeding vs expressed) is also expected to change.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained in a study performed in Kielce region, Poland (34.1%), as well as those reported in a nationwide German survey (27.8%). This may suggest that PUFA are not commonly known in society [3,26].…”
Section: Source Of Knowledge About Proper Nutrition During Pregnancymentioning
confidence: 99%